Metabolome and Transcriptome Analysis of Liver and Oocytes of Schizothorax o’connori Raised in Captivity - Zhou, Jianshe; Wang, Wanliang; Li, Zhichao; Zhang, Chi; Wan, Zhiyi; Sun, Shuaijie; Zeng, Benhe; Li, Ming; Sun, Guirong (Frontiers in Genetics, 2021)
Schizothorax o’connori (S. o’connori) is a representative tetraploid species in the subfamily Schizothoracinae and an important endemic fish in the Qinghai-Tibet Plateau. However, the domestication of S. o’connori remains challenging due to the lack of basic research. Here, we investigated the effects of artificial feeding on the oocytes and liver of S. o’connori by comparing the histological, metabolomic, and transcriptomic data. Histological results showed that the oocytes and liver of captive-reared S. o’connori had abnormal cell morphology. After comparison with the self-built database, a total of 233 metabolites were annotated. In oocytes, a total of 37 differentially accumulated metabolites (DAMs) were detected and 2 pathways were significantly enriched. There were obvious differences in the metabolites related to ovarian development, including pregnenolone, arachidonic acid, etc. In liver, a total of 70 DAMs were detected and 5 pathways were significantly enriched. Based on the transcriptomic data, a total of 159 differentially expressed genes (DEGs) were significantly related with cell growth and death pathway in oocytes, while a total of 2841 DEGs were significantly related with 102 pathways in liver. Comparing the metabolomic and transcriptomic data showed that there were 3 common significant enrichment pathways in liver, including biosynthesis of unsaturated fatty acids, starch and sucrose metabolism, and fatty acid biosynthesis. These results showed that special attention should be given to the composition and intake of fatty acids during the artificial breeding of S. o’connori. In addition, many of metabolite-gene pairs were related to adenosine 5'- diphosphate, adenosine monophosphate, and pregnenolone. In summary, these data provide an overview of global metabolic and transcriptomic resources and broaden our understanding of captive-reared S. o’connori.